Mass Communication in India - Keval J Kumar (Jaico, 1994)
The book has five sections. The first deals with a general introduction to communication theory. The second entitled \\\'Mass Media\\\' is divided into journalism, radio, television, cinema, advertising, public relations, folk media and group media. The third section is devoted to the psychology and sociology of the audience. The fourth section on \\\'The Effects of the Mass Media\\\' and the fifth on \\\'Media and Development\\\' deal with audience behaviour and the concept of development well supported by research studies. The book meets its objective of being a textbook as well as a book that gives an overview of mass communication in India.